Training Needs for Teachers from the Educational Professional Development Center (Journal Of Educational and Psychological Researches, 2022)
The research aims to characterize the strategic plan of the Educational Professional Development Center, to reveal the most important training needs for teachers from this center, to reveal the extent to which this center meets those needs, and to identify the differences between teacher responses about the degree of importance, availability of those needs according to variables of sex, specialization, and years of experience. This descriptive study adopted a questionnaire applied to (256) teachers in the K.S.A. The results of the study showed that all training needs ranged in the degree of importance from large to very large and that the most important were the skills associated with communicating with members of the learning community. While the degree to which the Educational Professional Development Center met these needs was moderate, and most of these needs were the skills associated with evaluation. The results also showed that there were statistically significant differences between the averages of teacher responses on the total questionnaire of the most important training needs for teachers, according to the variable of specialization for teachers with applied specialties, and according to the variable of years of experience for teachers with years of experience from 5 to less than 10 years. There were also differences between the averages of teachers ’responses to the total questionnaire of the degree of the educational professional development center meeting the teachers’ training needs, according to the sex variable for the male teachers, and according to the variable of specialization for teachers with religious and Arabic specializations.